The pair-wise province-to-county aid model for disaster relief - Wang, Zhenyao (International Food Policy Research Institute, 2016)
China first adopted a pair-wise aid policy, in which one donor province or city is assigned to a recipient area, in the 1950s as part of its efforts to develop the minority-inhabited border areas, and this practice was first formalized by the central government in 1979 (Qian et al. 2012). Since then, this strategy has also been used to undertake major infrastructure construction projects (such as the Three Gorges Dam in 1992) and disaster relief and recovery (such as that following the 1976 Tangshan earthquake), and China has continued to hone this method of coordinating the entire country to achieve key objectives. The integration of the pair-wise province-to-county aid model, in which a specific province is assigned to help a disaster-stricken county, into China’s disaster relief and reconstruction plans following the 2008 Wenchuan earthquake was a significant institutional innovation. According to the model, when several counties or cities are simultaneously hit by a major catastrophe, other relatively wealthy provincial governments of regions not stricken by the disaster use their resources to directly aid a certain county or city on a one-to-one basis. This chapter describes the disaster itself, the government’s response, and the policy innovation process behind the formulation of the pair-wise aid relief and reconstruction plan, and it provides additional insights on this policy and its implications.